Application of Ultra-deep Directional Drilling Technology in the Investigation of Sichuan—Tibet Railway Tunnel - Zhengxuan XU; Jianguo LIU; Jinsheng WU; Tao FENG; Minghao CHEN; Yandong WANG; Dong YUAN (工程科学与技术)
In view of the large terrain elevation difference along the Sichuan—Tibet railway, the steep topography of the long and large buried depth tunnel project, extremely poor traffic conditions, and the inability to implement vertical deep hole exploration, the existing directional exploration drilling rig has some shortcomings in the poor adaptability of railway survey in high mountain and canyon areas, and the directional exploration technology cannot meet the technical requirements of full-hole geological core coring in railway tunnel surveys. It is proposed to carry out research and development of ultra-long rope coring directional drilling tools and equipment, drilling technology and process, exploration model and railway super-long directional exploration application and demonstration project. Based on the summaries of the application status of ultra-deep directional drilling technology in the Sichuan—Tibet railway tunnel engineering survey, its development suggestions were put forward. The conclusions show that: 1) Through the research and development of ultra-deep horizontal directional exploration technology and equipment, the problem of horizontal deep-hole drilling equipment on the Sichuan—Tibet railway has been solved, and a set of horizontal rope directional drilling equipment and technology has been innovated, achieving zero domestic breakthroughs, and forming a set of ultra-long rope coring directional exploration method. 2) The self-developed GXD–5S kilometer-level full-hydraulic power-head directional drilling rig and super-long rope core directional drilling technology have been successfully applied to the Kazila Mountain No. 1 Tunnel of the Sichuan—Tibet railway and created a domestic horizontal rope as a demonstration project the two latest records of drill pipe PQ (diameter 122 mm) with depth 588 m and HQ (diameter 96 mm) with depth 974 m. 3) Through three survey modes of horizontal drilling, oblique drilling, and upside directional drilling, special geological factors for tunnel survey design in high mountains and valleys were constructed to obtain new geological models. 4) A total of 27 ultra-deep rope coring directional exploration drilling holes were completed in the Ya’an—Changdu section of the Sichuan—Tibet railway, of which the deepest horizontal directional drilling depth was 1888.88 m. Deep directional drilling technology provides a better support for the railway survey design and popularization and application.